Recent changes in Canadian-resident travel to the United States - Carter McCormack; Laura Presley (Economic and Social Reports)
This article highlights recent changes in transborder travel. It discusses the recent declines in Canadian-resident trips to the United States amid policy changes towards Canada implemented by the United States.